Problems of Professional Development of Managers and Teachers of Professional Educational Institutions Based on Adragogical Approaches - Khakimjonova, Kh. Kh. (European Journal of Life Safety and Stability (2660-9630), 2021)
The article deals with the problems of professional development of managers and teachers of professional educational institutions on the basis of adragogical approaches. The results of the study are included. Analyses of the conducted experiments in quantitative terms and conclusions drawn on quality indicators. Organizational and pedagogical conditions and stages of professional competence development, the influence of the developing training seminar on improving the level of knowledge, skills and abilities of managers are presented.